(untitled) (Journal of Brain and Spine Foundation Nepal, 2021)
Introduction: Stroke is one of the major causes of increased morbidity and death. Large-vessel atherosclerosis of intracranial and extra cranial carotid vessels is an important cause of ischemic stroke. This research was undertaken to study the carotid Doppler findings in patients with acute ischemic stroke. Methods: A hospital-based prospective cross-sectional study was conducted from January 2020 till December 2020 in the department of Radio diagnosis and Imaging at Manipal Teaching Hospital, Pokhara, Nepal. Neuro-imaging and carotid Doppler findings in patients with ischemic stroke were studied. Data analysis was done using SPSS 20. Results: The mean age of subjects with ischemic stroke was 64 ± 13.4 years with the majority of cases in the age group of 51-70 years of age with male predominance (M: F= 3: 2). Lacunar infarcts (34.2%) were the most common findings followed by MCA infarct (30%) and ACA infarct (10.8%). Carotid plaques were seen in 43.3% patients. Bilateral ICA atheromatous plaque was seen in 48.1% of patients. Carotid bulb was the common site for plaque formation. Type III plaque was the commonest type. Significant ICA stenosis > 50 % was observed in 24.2% patients. Age >50 years, male sex, smoking, hypertension, diabetes, and hyperlipidemia were important risk factors. Conclusion: Carotid artery Doppler demonstrated atherosclerotic plaques and significant stenosis in patients with ischemic stroke. Increasing age >50 years, male sex, smoking, hypertension, diabetes, and hyperlipidemia were associated with an increased rate of atherosclerosis, carotid stenosis and ischemic stroke.